1998
DOI: 10.1101/gad.12.9.1381
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of crossing-over by DNA methylation in Ascobolus

Abstract: Homologous recombination between dispersed DNA repeats creates chromosomal rearrangements that are deleterious to the genome. The methylation associated with DNA repeats in many eukaryotes might serve to inhibit homologous recombination and play a role in preserving genome integrity. We have tested the hypothesis that DNA methylation suppresses meiotic recombination in the fungus Ascobolus immersus. The natural process of methylation-induced premeiotically (MIP) was used to methylate the b2 spore color gene, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
100
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(108 citation statements)
references
References 50 publications
(68 reference statements)
7
100
0
1
Order By: Relevance
“…Several examples of recombination events between repeats have been identi®ed in the human population and these have had deleterious consequences (Puget et al, 1997;Rouyer et al, 1987;Small et al, 1997). Work with the fungus Ascobolus immersus has demonstrated that induced methylation of a meiotic recombination hotspot reduced the frequency of crossing-over within this region by several hundredfold (Maloisel and Rossignol, 1998). The most direct evidence that DNA methylation suppresses homologous recombination has come from the work in Ascobolus, but several studies support a similar role in mammalian cells.…”
Section: Dna Hypomethylation ± Roles In Cancer and Genome Stabilitymentioning
confidence: 96%
“…Several examples of recombination events between repeats have been identi®ed in the human population and these have had deleterious consequences (Puget et al, 1997;Rouyer et al, 1987;Small et al, 1997). Work with the fungus Ascobolus immersus has demonstrated that induced methylation of a meiotic recombination hotspot reduced the frequency of crossing-over within this region by several hundredfold (Maloisel and Rossignol, 1998). The most direct evidence that DNA methylation suppresses homologous recombination has come from the work in Ascobolus, but several studies support a similar role in mammalian cells.…”
Section: Dna Hypomethylation ± Roles In Cancer and Genome Stabilitymentioning
confidence: 96%
“…DNA methylation also represses CO formation (Maloisel and Rossignol 1998) and is sufficient to silence CO hotspots in Arabidopsis (Yelina et al 2015). CO distribution is largely modified in Arabidopsis met1 and ddm1 mutants, which show an increase of proximal recombination events and a simultaneous decrease in pericentromeric and distal regions (Colome-Tatche et al 2012;Melamed-Bessudo and Levy 2012;Mirouze et al 2012;Yelina et al 2012).…”
Section: Retrotransposons Associate With Reduced Recombination Ratementioning
confidence: 99%
“…Long repeats including LINE-1 elements are normally heavily DNA-methylated (Woodcock et al, 1988;Crowther et al, 1991;Woodcock et al, 1997), a feature of heterochromatin. DNA methylation (and heterochromatin in general) has been reported to suppress homologous recombination (Pàldi et al, 1995;Maloisel and Rossignol, 1998;Schnable et al, 1998;Fu et al, 2002;Yao et al, 2002;Yamada et al, 2004;Myers et al, 2005) as well as transposition (Yoder et al, 1997;Walsh et al, 1998;Hirochika et al, 2000;Robertson, 2001;Bird, 2002;Kato et al, 2003). Accordingly, reports of deletions caused by homologous recombination between LINE-1 elements are rare (Segal et al, 1999) except in cancers (Florl and Schulz, 2003) where LINE-1 elements are frequently hypomethylated (Santourlidis et al, 1999;Takai et al, 2000;Ehrlich, 2002;Carnell and Goodman, 2003;Florl et al, 2004;Roman-Gomez et al, 2005).…”
Section: Non-random Repeat Distributions Via Natural Selectionmentioning
confidence: 99%